2010
DOI: 10.1080/03081061003643747
|View full text |Cite
|
Sign up to set email alerts
|

Consumer learning behavior in choosing electric motorcycles

Abstract: The purpose of this paper is to understand the effect of the learning process on consumers' choice behavior for electric motorcycles in Taiwan. The electric motorcycle is a new technological product so consumers need to gather all kinds of information Á performance, operating cost, government subsidy policy, etc. Á to reduce their uncertainty about the product. In this paper, a four-stage stated preference experiment is designed and a survey applied. At each stage, the survey gives respondents new information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…This indicates that when consumers believe that EVs are more beneficial at the individual, environment or national level, or they believe that the usage of these vehicles is simpler and more convenient, they will show a more willingness to adopt or buy such vehicles. In the similar disposition, individuals with high levels of product knowledge with sufficient information may reduce the potential risks, which could considerably improve their behavioural intentions to adopt EVs (Wang et al, 2018;Sung, 2010). Therefore, subjective knowledge of product may enable consumers to fine-tune their strategy to avoid the risk related to the adoption of such product.…”
Section: Knowledge About Electric Vehiclesmentioning
confidence: 99%
“…This indicates that when consumers believe that EVs are more beneficial at the individual, environment or national level, or they believe that the usage of these vehicles is simpler and more convenient, they will show a more willingness to adopt or buy such vehicles. In the similar disposition, individuals with high levels of product knowledge with sufficient information may reduce the potential risks, which could considerably improve their behavioural intentions to adopt EVs (Wang et al, 2018;Sung, 2010). Therefore, subjective knowledge of product may enable consumers to fine-tune their strategy to avoid the risk related to the adoption of such product.…”
Section: Knowledge About Electric Vehiclesmentioning
confidence: 99%
“…They found that males' and females' perceptions toward such choice decisions vary significantly. In another Taiwan-based research study, Sung et al [28] employed a Bayesian learning model to understand the consumers' choice behavior for E2Ws. They found the quality of E2Ws to be a guiding attribute.…”
Section: Literature Review and Research Scopementioning
confidence: 99%
“…This methodology would provide insights to both manufacturers and prospective users for informed decision-making specific to E2W. The majority of the past studies in the context of E2W in general, and E2W attribute valuation, in particular, has been taken up in developed countries such as China [62], USA [14,63], and Norway [64] or countries where E2W is already a popular or established mode of transport such as Taiwan [28,65] and Indonesia [11]; however, due to the significant difference in the transport and socio-economic characteristics of commuters, results derived from such studies cannot be directly applicable to a country such as India, where E2W is at its nascent stage. Hence, this methodology and related findings would be a distinct contribution to the body of E2W commuting specific research literature in general, in the context of India in particular.…”
mentioning
confidence: 99%
“…The environmental gains related to electrification of large urban motorized two‐wheeler vehicle fleets have been demonstrated by the outcomes of several research studies (Amjad et al ; Sung ; Weinert et al ); however, none has considered the life cycle environmental burden of the urban charging network for E2Ws, even though they constitute the most successful electric‐drive market in the world (Weinert et al ).…”
Section: Introductionmentioning
confidence: 99%